FBXO22 Promotes Growth and Metastasis and Inhibits Autophagy in Epithelial Ovarian Cancers via the MAPK/ERK Pathway - Minle Li; Xue Zhao; Xue Zhao; Hongmei Yong; Bingqing Shang; Weihua Lou; Weihua Lou; Weihua Lou; You Wang; You Wang; You Wang; Jin Bai; et al. (Frontiers Media S.A., 2021)
E3 ubiquitin ligase F-box only protein 22 (FBXO22), which targets the key regulators of cellular activities for ubiquitylation and degradation, plays an important role in tumorigenesis and metastasis. However, the function of FBXO22 in epithelial ovarian cancers has not been reported. This study aims to explore the biological function of FBXO22 in epithelial ovarian cancers progression and metastasis and its specific regulation mechanism. Immunohistochemistry analysis of tissue microarray was performed to evaluate the expression of FBXO22 in epithelial ovarian cancers patients. The proliferative ability of epithelial ovarian cancers cells was examined by the CCK8. The metastasis ability was detected by the wound healing assay, migration and invasion assays. Western blot was used to verify the relationship between FBXO22 expression and mitogen-activated protein kinase related proteins. Autophagic flux was detected by electron microscopy, mRFP-GFP-LC3 adenovirus, lysosomal tracker and western blot. For in vivo experiments, the effect of FBXO22 on epithelial ovarian cancers resistance was observed in a xenograft tumor model and a metastatic mice model. We found that FBXO22 expression was significantly increased in epithelial ovarian cancers tissues and was closely correlated with clinical pathological factors. As a result, we found that FBXO22 promoted the growth and metastasis, as well as inhibited the autophagy flux. In addition, we identified that FBXO22 performed these functions via the MAPK/ERK pathway. Our results first reported the function of FBXO22 in epithelial ovarian cancer and the correlation between FBXO22 and autophagy, suggesting FBXO22 as a novel target of epithelial ovarian cancers assessment and treatment.